NUT Carcinoma—An Underdiagnosed Malignancy - Lauer, Ulrich M.; Hinterleitner, Martina; Horger, Marius; Ohnesorge, Paul V.; Zender, Lars (Frontiers in Oncology, 2022)
NUT carcinoma (NC) is a rare and highly aggressive malignancy with a dismal prognosis and a median survival of six to nine months only. Although very few cases of NC are reported each year, the true prevalence is estimated to be much higher, with NC potentially widely underdiagnosed due to lack of awareness. NC primarily occurs in midline structures including thorax, head and neck; however, other sites such as pancreas and kidney are also affected, albeit at lower frequencies. NC is characterized by a single translocation involving the NUTM1 (NUT midline carcinoma family member 1) gene and different partner genes. The resulting fusion proteins initiate tumorigenesis through a mechanism involving BET (bromo-domain and extra-terminal motif) proteins such as BRD4 and inordinate acetylation of chromatin, leading to dysregulation of growth and differentiation genes. While no clinical characteristics are specific for NC, some histologic features can be indicative; therefore, patients with these tumor characteristics should be routinely tested for NUTM1. Diagnosis of NC using immunohistochemistry with a highly specific antibody is straightforward. There are currently no standard-of-care treatment options for patients with NC. However, novel therapies specifically addressing the unique tumorigenic mechanism are under investigation, including BET inhibitors. This review aims to raise awareness of this underdiagnosed cancer entity and provide all patients the opportunity to be properly diagnosed and referred to a clinical study.